Micheliolide attenuates sepsis-induced acute lung injury by suppressing mitochondrial oxidative stress and PFKFB3-driven glycolysis - Wenhan Li; Yuhan Li; Linjie Xiao; Zhanzhan Xie; Jun Peng; Wenhui Huang; Xu Li; Ying Meng (Journal of Translational Medicine)
Abstract Background Sepsis is a potentially fatal condition with a significant risk of death. Acute lung injury (ALI) is a life-threatening complication of sepsis, and the inflammatory response plays a critical role in sepsis-induced ALI. The protective effects of micheliolide (MCL) against renal fibrosis and leukemia have been demonstrated, but the precise underlying mechanisms remain unclear. Methods In vitro, lipopolysaccharides (LPS) and interferon-gamma (IFN-γ) were used to stimulate RAW264.7 cells and bone marrow-derived macrophages (BMDMs) to investigate the protective effect of MCL on sepsis-induced ALI. Cecal ligation and puncture (CLP) models were constructed in mice to induce ALI in vivo. The expression of inflammatory factors, macrophage polarization markers, and the glycolysis-related enzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) were measured in vivo. Mitochondrial function, oxidative stress, and mitochondrial-related proteins were evaluated in vitro. Results MCL inhibited CLP-induced ALI, as evidenced by improvements in proinflammatory factor levels, lung wet/dry ratios, and histopathological findings. In vitro, MCL treatment significantly suppressed LPS + IFN-γ-induced M1-type polarization of RAW264.7 cells and BMDMs, as well as the production of inflammatory factors and oxidative stress. Mechanistic experiments revealed that MCL suppresses PFKFB3-driven glycolysis to reduce inflammation and activates the mitochondrial unfolded protein response (UPRmt) to alleviate mitochondrial stress. However, the therapeutic effect of MCL was diminished when PFKFB3 was overexpressed in cells. Conclusion This study is the first to demonstrate that MCL attenuates sepsis-induced ALI by reducing M1-type macrophage polarization. Its therapeutic effect is closely related to the suppression of oxidative stress and PFKFB3-driven glycolysis.